2008
DOI: 10.1016/j.neubiorev.2007.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Is exposure to enriched environment beneficial for functional post-lesional recovery in temporal lobe epilepsy?

Abstract: Exposure to environmental enrichment has been shown to induce robust neuronal plasticity in both intact and injured adult central nervous system, including up-regulation of multiple neurotrophic factors, enhanced neurogenesis in the dentate gyrus of the hippocampus, and improved spatial learning and memory function. Neuronal plasticity, though mostly adaptive and abnormal, also occurs during certain neurodegenerative conditions such as the temporal lobe epilepsy (TLE). The TLE is characterized by hippocampal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 220 publications
2
40
0
1
Order By: Relevance
“…These toys and positions were changed 1-2 times/week to bestow environmental novelty. The enrichment also comprised increased social interaction, as larger numbers of animals (about 10 rats in our experiment) were usually housed together in bigger and wider cages with exploratory chambers (Dhanushkodi and Shetty 2008;Fares et al 2013).…”
Section: Effects Of Ee On Aberrant Hippocampal Neurogenesis and The Ementioning
confidence: 95%
See 1 more Smart Citation
“…These toys and positions were changed 1-2 times/week to bestow environmental novelty. The enrichment also comprised increased social interaction, as larger numbers of animals (about 10 rats in our experiment) were usually housed together in bigger and wider cages with exploratory chambers (Dhanushkodi and Shetty 2008;Fares et al 2013).…”
Section: Effects Of Ee On Aberrant Hippocampal Neurogenesis and The Ementioning
confidence: 95%
“…9 A summary figure explaining the possible molecular mechanisms and pathways of EE treatment on chronic TLE. Status epilepticus results in multiple pathological changes including hippocampal neurons loss, aberrant sprouting of mossy fibers, and spontaneous recurrent seizures, which eventually lead to declined DG neurogenesis and cognitive impairment in chronic TLE (Dhanushkodi and Shetty 2008). It should be noted that the role of aberrant mossy fibers sprouting in epileptogenesis remains controversial (Scharfman et al 2003;Sloviter et al 2006;Buckmaster 2014).…”
Section: Effects Of Ee On the Srs And Cognitive Functions After Tlementioning
confidence: 99%
“…Nevertheless, in our study, we observed a complete preservation of hippocampal cytoarchitecture and functional recovery when HEK-CM was injected 72 h after KA-induced hippocampal injury. The discrepancy may be caused by prolonged BBB opening after KA injection, owing to its seizure-inducing potential [1,17]. Thus, to utilize the beneficial effects of cell-based therapy for various neurodegenerative diseases, it is important to understand the pattern and duration of BBB disruption for a given neurodegenerative condition that would help us to identify an appropriate therapeutic window for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal neurodegeneration is one of the hallmarks in neurological and neurodegenerative diseases such as temporal lobe epilepsy and Alzheimer disease [1,2]. Excitotoxicity caused by augmented release of glutamate plays a significant role in neuronal losses in these disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this, a range of studies have demonstrated that administration of neurotrophic factors to both the normal and injured adult rodent brain can enhance hippocampal neurogenesis (Lichtenwalner, et al, 2001, Yoshimura, et al, 2001, Scharfman, et al, 2005, Rai, et al, 2007, Paradiso, et al, 2009, Paradiso, et al, 2011. Performing physical exercise and environmental enrichment have also been shown to enhance hippocampal neurogenesis, potentially through increased expression of a range of mitogenic factors such as BDNF, FGF2, NGF, IGF-1 and VEGF as well as phosphorylation of cAMP-response binding protein (CREB) (Nithianantharajah, et al, 2006, Van Praag, 2008, Llorens-Martín, et al, 2009, Lafenetre, et al, 2011 and may provide an appealing noninvasive therapeutic approach for the treatment of chronic TLE (Dhanushkodi, et al, 2008, Arida, et al, 2009. Antidepressant therapy in chronic TLE is another interesting approach for increasing neurogenesis and reducing cognitive impairments, as antidepressant therapy enhances hippocampal neurogenesis probably via increases in levels of serotonin, noradrenaline, BDNF, CREB and a range of other mitogenic factors (Sahay, et al, 2007, Thomas, et al, 2008, Lanni, et al, 2009.…”
Section: Chronic Tlementioning
confidence: 99%